2016
DOI: 10.1007/s13277-016-4810-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of 188Re-labeled NGR–VEGI protein for radioimaging and radiotherapy in mice bearing human fibrosarcoma HT-1080 xenografts

Abstract: Vascular endothelial growth inhibitor (VEGI) is an anti-angiogenic protein, which includes three isoforms: VEGI-174, VEGI-192, and VEGI-251. The NGR (asparagine-glycine-arginine)-containing peptides can specifically bind to CD13 (Aminopeptidase N) receptor which is overexpressed in angiogenic blood vessels and tumor cells. In this study, a novel NGR-VEGI fusion protein was prepared and labeled with (188)Re for radioimaging and radiotherapy in mice bearing human fibrosarcoma HT-1080 xenografts. Single photon em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 42 publications
4
18
0
Order By: Relevance
“…The radiolabelling of NGR probes by diagnostic and therapeutic radionuclides (e.g. : 64 Cu (Li et al, 2014), 68 Ga (Máté et al, 2015;Satpati et al, 2017), 99m Tc (Vats et al, 2017), 177 Lu (Vats et al, 2018), 188 Re (Ma et al, 2016)) provides an opportunity to monitor the in vivo biodistribution and tumor-targeting properties of the novel NGR derivatives, furthermore, give the possibility to follow the efficacy of anti-cancer therapies using in vivo molecular imaging. In addition, the detection of the APN/CD13 molecule is particularly important because it has been observed that it is not only a diagnostic but also a prognostic marker, that may predict the mortality and overall survival (Kessler et al, 2018;Schreiber et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The radiolabelling of NGR probes by diagnostic and therapeutic radionuclides (e.g. : 64 Cu (Li et al, 2014), 68 Ga (Máté et al, 2015;Satpati et al, 2017), 99m Tc (Vats et al, 2017), 177 Lu (Vats et al, 2018), 188 Re (Ma et al, 2016)) provides an opportunity to monitor the in vivo biodistribution and tumor-targeting properties of the novel NGR derivatives, furthermore, give the possibility to follow the efficacy of anti-cancer therapies using in vivo molecular imaging. In addition, the detection of the APN/CD13 molecule is particularly important because it has been observed that it is not only a diagnostic but also a prognostic marker, that may predict the mortality and overall survival (Kessler et al, 2018;Schreiber et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The development of radio-labeled peptide probes, such as RGD and NGR, for diagnostic and therapeutic applications, has rapidly expanded in the last decades (34)(35)(36)(37). On the aspect of clinical practice, the safety and the applicability of these probes have been well established in lung cancer (38)(39)(40), brain metastases (41), breast cancer (42) and rheumatoid arthritis (43).…”
Section: Discussionmentioning
confidence: 99%
“…188 Re has similar chemical characteristics as 99m Tc but emits an electron in addition to gamma lines that are suitable for SPECT—making the isotope suitable for radionuclide therapy. They demonstrated a favourable tumour to background ratio in HT-1080 tumour xenografts using SPECT, and more importantly showed that when applied in therapeutic concentrations [ 188 Re]Re-NGR-VEGI showed excellent tumour inhibition effect with no observable toxicity [ 157 ]. Zhao et al combined RGD with Evans blue and subsequently labelled this peptide analogue with 177 Lu, another therapeutic isotope.…”
Section: Beyond Imagingmentioning
confidence: 99%